Implementation of the “Kampung Bebenah Desa Sejahtera” Policy in Kopo Village, Kutawaringin Subdistrict, Bandung Regency - Nuraeni, Siti; Mariah, Siti Lainufar (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Environmental degradation caused by poor waste management remains a pressing challenge in Indonesia, particularly at the village level where rapid population growth intersects with limited infrastructure. Responding to this urgency, the Bedas Village Program in Bandung Regency was introduced to foster community-based environmental governance and improve local welfare. This study aims to analyze the implementation of the program in Kopo Village using Jones’ tripartite model of policy implementation, focusing on organizational, interpretative, and applicative dimensions. Employing a qualitative descriptive approach, data were collected through observation, semi-structured interviews, and document analysis, and subsequently analyzed with Miles and Huberman’s interactive model. The findings reveal that while organizational structures and innovative practices such as maggot cultivation and LCO adoption have shown promise, gaps remain in community comprehension, resource distribution, and sustainability of participation. These results highlight the need for stronger institutional support, continuous capacity building, and inclusive communication strategies to ensure long-term program effectiveness.